1966
DOI: 10.4039/ent981284-12
|View full text |Cite
|
Sign up to set email alerts
|

The Trichoptera of St. Helen's Island, Montreal: I. The Species Present and Their Relative Abundance at Light

Abstract: St. Helen's Island, the site of Trichoptera studies in 1964 and 1965, is described. The Trichoptera encountered are listed, and taxonomic notes given where appropriate. Catches from a light-trap operated nightly in each year provide information for the different species concerning: relative abundance, frequency and seasonal range of occurrence, pest status, and sex ratio. Of the 99 species recorded, eight were classified as pests (causing a nuisance at light), six having this status in both years; together the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Figure 4 shows the cumulative emergence of both males and females of six common species. The analysis of nightly sex ratios of caddisflies collected at light traps by Corbet et al (1966) revealed no consistent changes correlated with the time of year that would indicate whether either sex had an earlier emergence period. penitum are mean rates for the 3 years but only for the autumn emergence, as the start of the spring emergence was not collected in 1968.…”
Section: Sex Ratios and Timing Of Emergencementioning
confidence: 93%
See 1 more Smart Citation
“…Figure 4 shows the cumulative emergence of both males and females of six common species. The analysis of nightly sex ratios of caddisflies collected at light traps by Corbet et al (1966) revealed no consistent changes correlated with the time of year that would indicate whether either sex had an earlier emergence period. penitum are mean rates for the 3 years but only for the autumn emergence, as the start of the spring emergence was not collected in 1968.…”
Section: Sex Ratios and Timing Of Emergencementioning
confidence: 93%
“…It is apparent that results from light trap collections are largely a measure of activity and that the sex ratio from specimens collected by this method is not necessarily that existing at emergence (Crichton 1960;Corbet et al 1966;Ulfstrand 1970). It is apparent that results from light trap collections are largely a measure of activity and that the sex ratio from specimens collected by this method is not necessarily that existing at emergence (Crichton 1960;Corbet et al 1966;Ulfstrand 1970).…”
Section: Sex Ratios and Timing Of Emergencementioning
confidence: 99%
“…The mean (arithmetic) catch volume of 74 nll per evening throughout 1967 (Table VIII) is substantially lower than the threshold value of 100 rnl that was reported by Corbet et al (1966) to indicate a local density of flying insects capable of creating a nuisance to man, and indicates that in general the objective of the larviciding program was attained. This also was the general opinion of members of our staff and certain employees of Expo 67 who made personal observations almost every day and evening throughout the summer of 1967 and noted that shadfly accumulations were rarely seen on the site.…”
Section: February 1972mentioning
confidence: 54%
“…1 and has been described by Corbet et al ( 1966) andFredeen ( 1969). 1 and has been described by Corbet et al ( 1966) andFredeen ( 1969).…”
Section: Introductionmentioning
confidence: 99%
“…These differences were not entirely due to different collecting methods even though at St. Helen's Island the Trichoptera were collected in a very effective light trap consisting of a 125-w mercury-vapor lamp in a metal cone over a bucket of alcohol (Corbet et al 1966) whereas at Fort Erie they were collected in emergence cages and with sweep nets through swarms and shrubbery, and around incandescent lights at night (E. G. Munroe, pers. These differences were not entirely due to different collecting methods even though at St. Helen's Island the Trichoptera were collected in a very effective light trap consisting of a 125-w mercury-vapor lamp in a metal cone over a bucket of alcohol (Corbet et al 1966) whereas at Fort Erie they were collected in emergence cages and with sweep nets through swarms and shrubbery, and around incandescent lights at night (E. G. Munroe, pers.…”
Section: The Fauna At Fort Erie and Montrealmentioning
confidence: 99%